PENGARUH MEDIA PETA INTERAKTIF TERHADAP PEMAHAMAN DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV SD - Maya Kartika Sari (Universitas PGRI Madiun, 2014)
Teaching media has been applied and studied since long ago, but the significance of interactive map media in teaching social science at elementary school has not yet developed. This research is attempted to depict: the students’ mastery on the places and sites, activeness and achievement. The research is conducted under two-cycle class action research on 30 students of four grade, SD Jetis, Bantul, Jogjakarta, at social science subject. The analysis brings about results that: (1) the students’ mastery increases, from 4 students in preliminary reserach becomes 11 in the first cycle and 26 in the second cycle of the research, who master the teaching materials. (2) Students’ activeness increases from 5 students in the prilimary research, to 10 in the first cycle and 28 in the second cycle, who are active in classes. (3) The students’ achievement also increase from 6 students to 15 in the first cycle and 29 in the second cycle, who achieve better mark. The results suggest that interactive map is effective in teaching social science for the students of four grade. Keywords : teaching social science, interactive map media.